If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1
(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)
2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1
3a + 4b - 5 - 1a + 7b + 3 - 1b 2a + 10b - 5 + 3 2a + 10b - 2
depends what 'a' =
2a + 4b - 52a + 4b - 52a + 4b - 52a + 4b - 5
The problem 3a-1 and 2a-5 is greater by 7. This is a math problem.
5a - 5 = 7 + 2a ( subtract 2a from both sides) 3a - 5 = 7 (add 5 to both sides) 3a = 12 ( divide both sides by 3) a = 4
5a³ - 4ab + 2a³ = (5+2)a³ - 4ab = 7a³ - 4ab.
The idea here is to combine terms that have the same variable (or, in more complicated cases, the same combination of variables). For example, 3a + 2a is the same as 5a.
= 3 X 2 = 6 = a X a = a2 (a square) = 6a2 + 5 Answer
5 x 3a= 15a
12(8a + 28) + 2a + 5 84a + 336 + 2a + 5 86a + 341
To my opinion and search, I believe that 3a+5 can be written as 3/5 a
is that ment to be a > sign? well if it is3a>4a-5 (-4a)-a>-5 then just inverta>5
3a + a = 4a Example: a = 5 (3x5) + 5 = 15 + 5 = 20 = 4 x 5
2a + 7b = -13a - 7b = -5The system of equations can be solved by elimination:2a + 3a = -65a = -6a = -6/5substitute the value of a in any of the two original equations to find the value of b:2(-6/5) + 7b = -1-12/5 + 1 = -7b-7/5 = -7bb= 1/5
a2+3a-10 = (a-2)(a+5) when factored